Large-scale societal factors and noncommunicable diseases: Urbanization, poverty and mortality spatial patterns in Argentina. (September 2017) - Pou, Sonia Alejandra; Tumas, Natalia; Sánchez Soria, David; Ortiz, Pablo; Díaz, María del Pilar
Abstract: Introduction: In developing countries, the rapid increase in noncommunicable diseases burden has been accompanied by socio-demographic changes, such as rapid urbanization, with persistence of considerable socio-economic gaps between populations. In Argentina, cardiovascular diseases (CVD) and cancer are leading causes of death. The aim of this study was to identify geographic clustering of mortality rates related to both diseases in Argentina and to assess their association with two large-scale societal factors, urbanization and poverty contexts. Materials and methods: We performed an ecological study in Argentina (n = 525 counties), 2009–2011 period. Using spatial analysis techniques we identified and mapped spatial clusters of high and low values for age-standardized mortality rates (ASMR) of cancer or CVD and for selected urbanization and poverty indicators. We estimated incidence-rate ratios using two-level Poisson regression models, which accounted for rates distribution spatial variability. Results: Cancer and CVD mortality rates distribution were spatially dependent. Population growth showed an inverse association with ASMR from these causes, for both sexes. We detected an additive interaction of effects between urban scale and poverty level, being the "rural poverty" associated with an increasing risk of mortality by cancer (in both sexes) or by CVD (only men), compared to contexts with high urban scale and low poverty level. Counties with an intermediate urban scale seem to present the most favorable context, even when their socio-economic conditions are more unfavorable than those with higher urbanization levels. Conclusions: Geographical differences in urban and socioeconomic contextual conditions can explain spatial variation in NCD mortality burden in Argentina. Highlights: There was a non-random spatial distribution of NCD mortality rates in Argentina. Differences between sexes were found for high-value spatial clusters of cancer. Urbanization and poverty are large-scale societal factors related to NCD mortality. Rural poverty was associated with higher cancer and CVD mortality rates. An intermediate urban scale seem to present the most favorable context.